2022
DOI: 10.1177/11206721221113199
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Status in the Pathogenesis of Primary Open-Angle Glaucoma, Pseudoexfolyation Syndrome and Glaucoma

Abstract: Purpose To investigate the role of oxidative stress and antioxidant system in the etiopathogenesis of pseudoexfoliation and progression of pseudoexfoliation syndrome to glaucoma. Material and method A total of 20 patients with pseudoexfoliation syndrome, 20 with pseudoexfoliation glaucoma, 20 with primary open-angle glaucoma, and 20 without pseudoexfoliation and glaucoma as a control group, who underwent cataract or glaucoma surgery between December 2020 and March 2021 in the Health Sciences University Beyoğlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Oxidative stress (OS) and hypoxia occurring in the tissue are the main factors activating the pathophysiologic process in PEX-S.[ 3 ] OS caused by impaired local oxidative/antioxidative balance results in local inflammation, thereby leading to proinflammatory cytokines being released and the inflammatory reaction being activated. [ 26 27 ] In fact, this inflammation is the outcome of the cumulative effect of OS and impaired endothelial function. Since inflammation in PEX-S is more of a localized inflammation, sensitive inflammatory markers that specifically indicate localized inflammation will be more useful to detect the inflammation present.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress (OS) and hypoxia occurring in the tissue are the main factors activating the pathophysiologic process in PEX-S.[ 3 ] OS caused by impaired local oxidative/antioxidative balance results in local inflammation, thereby leading to proinflammatory cytokines being released and the inflammatory reaction being activated. [ 26 27 ] In fact, this inflammation is the outcome of the cumulative effect of OS and impaired endothelial function. Since inflammation in PEX-S is more of a localized inflammation, sensitive inflammatory markers that specifically indicate localized inflammation will be more useful to detect the inflammation present.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is a multifactorial disease characterized by progressive damage to the retinal ganglial cells (RGCs) and consequent visual impairment (1). Many pathological processes, including oxidative stress, chronic neuroinflammation, mechanical damage with elevated intraocular pressure (IOP), mitochondrial dysfunction, impaired micro-circulation, and extracellular matrix remodeling have been found to contribute to its irreversible damage to the retina yet the associated mechanisms remain elusive (2)(3)(4). Due to the complexity, chronicity, and irreversibility of glaucoma, current medical and surgical treatment which is mainly based on IOP management fail to provide sufficient efficacy in a number of patients who progress to end-stage glaucoma and suffer from poor vision and chronic pain (5).…”
Section: Introductionmentioning
confidence: 99%
“…The exact etiopathogenesis of this condition is not yet completely understood, but it is considered a multifactorial disorder that develops through a complex interplay of environmental factors, such as UV exposure and geographic latitude, dietary factors, viral infection and trauma involving the anterior segment of the eye, along with genetic predisposition. Current studies have shown that factors associated with oxidative stress and antioxidant defense mechanisms can play important roles in the etiopathogenesis of PEX [ 10 , 11 ]. Recently, mutations in the lysyl oxidase-like 1 gene ( LOXL1 ) at the locus 15q22 have been identified as the major contributing factor to the fibrotic disorder seen in PEX syndrome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%